(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
The paper focuses on the custom automation system of a test bench for diesel engines used on navy ships, namely on tugboats. The test bench, with its automation system, is developed for practical training at a naval academy. The test bench aims to meet the highest standards in the education of Navy students and personnel. It facilitates undertaking practical laboratory works regarding the main constructive elements, operation, monitoring, and maintenance of four-stroke internal combustion engines, of the gearbox, as well as of the propeller load simulated by a hydraulic brake. The custom-made automation control system includes a modular cabinet with drives and automation sections, featuring a local command console for engine control and a remote command console for the entire test bench, with a large display for parameter monitoring.